A Administração Local comoFator de Desenvolvimento. Os municípios (comuni) da Itália Meridionale o controle de gestão - Fabrizio Battistelli (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2003)
Inverting the historical trend in the politics-institutional analyses of the Italian reality, and inspecial attention to the South of Italy, the present article approaches the questions of therelations policy system/social system valuing the ways the implementation of the decisions and giving it has not detached to the ends that public problems to only attack as ofcustom the theoreticians have boarded the subject. In this direction, stand out the role thatreforms, apparently techniques, as it is the management control, would have in the processof institutional changes that, at the same time, is cultural learning, economic, social andpolitician development.